Analisis Kepuasan Konsumen dan harga terhadap Loyalitas Pelanggan - Dina Apriani; Asep Muhammad Ramdan; Dicky Jhoansyah (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
Competition among local shoe users in retaining consumers and attracting new consumers is a challenge for business people. As one of the efforts to get loyal customers, the local shoe business must develop strategies to attract consumers, including increasing customer satisfaction and also pricing strategies. This study aims to analyze the effect of consumer satisfaction and price on customer loyalty of local shoe users in Sukabumi City. The method in this study used an associative descriptive method with quantitative use. The population in this study were users of local Ventela brand shoes in the city of Sukabumi, the sampling technique was probability sampling with random sampling, and the number of samples in this study was 252 respondents. Data analysis techniques in this study used the correlation coefficient, determination coefficient, simultaneous test (F test), multiple linear regression, and partial test (t-test). The results of the simultaneous analysis show that consumer satisfaction has a positive effect on customer loyalty, and this is consistent with prices which indicate that prices partially have a positive and significant effect on customer loyalty. Keywords: Consumer Satisfaction; Price; Customer Loyalty